REVISIÓN BIBLIOGRÁFICA: DISEÑO E INNOVACIÓN EN LAS AULAS PARA EL APRENDIZAJE DEL INGLÉS (2023)
This review describes the implementation of Virtual Learning Units (VLU) in the teaching of English language, based on the analysis of ten articles. Considering the needs coming up around modern society, which requires a new generation of teachers adapted to technological tools to encourage critical thinking and creativity of students in their training process. Methodology: A literature review was performed based on the search of materials in search engines such as Dialnet, Google Academic, Mendeley and Scielo,between 2019 and 2023. Results: Articles scientific were taken for the analysis of the results with a percentage of 70% international from countries such as Peru, Venezuela, Ecuador, Spain, Cuba and 30% Colombian. The use of virtual tools for learning the English language has a positive impact on students as they are motivated and involved in the development and use of these tools. Conclusions: The use and implementation of virtual tools for the teaching and learning process is determined, having as main objective to improve communicative skills in English, starting from the fact that these tools facilitate the use of new methodologies and strategies in the classroom.